The Misery Index Revisited: The Case Of Sukuk Issuing Countries - Nursilah Ahmad; Umi Hamidaton Mohd Soffian Lee; Syazwani Abd. Rahim; Nur Ain Syahida Aira Mohd Riduan (Universiti Sains Islam Malaysia, 2024)
The Misery Index (MI) is an economic indicator calculated by adding the unemployment rate to the inflation rate for an economy. The assumption is that higher inflation and unemployment rate creates economic and social costs for a country. The present study estimates the MI indicator for 19 sukuk issuing countries. Data are annual covering the period of 1991 until 2019. The findings suggest that inflation is a pressing issue in Kazakhstan, Turkey, Sudan, Indonesia, Pakistan, Egypt, and Iran. Conversely, unemployment is more prominent in Egypt, Senegal, Saudi Arabia, Oman, Malaysia, Jordan, and Bahrain. To the policymakers, the MI estimations imply the effectiveness of policy stance over the years and indicate areas of policy improvements in curbing either inflation or unemployment or both.